Pablo Picasso In His Montmartre Studio, 1908 - Gelett Burgess (NC, 2026)
Pablo Picasso in Montmartre studio with his African sculpture collection, 1908
Droits : Licence indiquee par Wikimedia Commons
Keywords: peinture; peintres; artistes peintres; picasso; photo; archives photographiques; photographie; Art